Discrete vector light bullets in coupled χ3 nonlinear cavities. (October 2022) - Panajotov, Krassimir; Tlidi, Mustapha; Song, Yufeng; Zhang, Han
Abstract: We consider coupled weakly birefringent cavities filled-in with nonlinear Kerr material and subject to linearly polarized optical injection. Light propagation in such a system is described by a system of discrete Lugiato–Lefever-type equations for each linear polarization component of the electric field into each cavity, coupled by the cross-phase modulation terms and the neighboring waveguides field overlap integrals. We demonstrate that this system supports stable three-dimensional vector localized structures often called discrete vector light bullets. We consider both anomalous and normal dispersion and show that it results in the generation of, respectively, bright and dark discrete vector light bullets. Due to the polarization multistability of the system, we demonstrated coexisting light bullets with polarization at the light bullets peaks as different as predominantly linear to predominantly circular. We have shown that chaotic spatio-temporal dynamics can be realized even for such an injection strengths for which the light bullets distribution in the system is stationary by increasing the coupling strength C between the cavities.